1998
DOI: 10.1086/301685
|View full text |Cite
|
Sign up to set email alerts
|

NAGLU Mutations Underlying Sanfilippo Syndrome Type B

Abstract: Sanfilippo syndrome type B (mucopolysaccharidosis III B) is a rare autosomal recessive disease caused by deficiency of alpha-N-acetylglucosaminidase, one of the enzymes required for the lysosomal degradation of heparan sulfate. The gene for this enzyme, NAGLU, recently was isolated, and several mutations were characterized. We have identified, in amplified exons from nine fibroblast cell lines derived from Sanfilippo syndrome type B patients, 10 additional mutations: Y92H, P115S, Y140C, E153K, R203X, 650insC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 11 publications
4
41
1
Order By: Relevance
“…3 Another possible explanation is that the DNA structure leaves this area more vulnerable to mutagenic events than other parts of the gene. A suggested 16 crucial role of the carboxy end of the protein in enzyme structure/function cannot necessarily be assumed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Another possible explanation is that the DNA structure leaves this area more vulnerable to mutagenic events than other parts of the gene. A suggested 16 crucial role of the carboxy end of the protein in enzyme structure/function cannot necessarily be assumed.…”
Section: Discussionmentioning
confidence: 99%
“…3,10,15,16 We now report the analysis of the NAGLU alleles of 40 MPS IIIB patients revealing strong heterogeneity with 25 novel mutations and two polymorphisms identified, including one mutation (R643C) common amongst Dutch patients that is clearly associated with the attenuated form of the disease.…”
Section: Introductionmentioning
confidence: 91%
“…org), is responsible for cleaving the glycosidic bond found in the backbone of heparan and thus plays a key role in heparan recycling. More than 100 different mutations in the naglu gene have been associated with the MPS IIIB phenotype, and biochemical studies have confirmed the deleterious effects of many of these mutations (1)(2)(3)(4)(5)(6)(7)(8)(9). Despite having been cloned ÏŸ10 years ago, no structural or mechanistic data for NAGLU have been obtained, hindering the development of potential therapeutic strategies to treat patients suffering from MPS IIIB.…”
mentioning
confidence: 99%
“…Two siblings with an attenuated phenotype were compound heterozygous for R565P/F314L, and one patient with a severe phenotype was homozygous for R565P. To our knowledge, excluding Tanaka's report, 88 different mutations have been reported in 116 MPS IIIB patients, and 39 patients showed homozygous mutations Schmidtchen et al 1998;Beesley et al 1998;Bunge et al 1999;Weber et al 1999;Tessitore et al 2000). In previous reports, no apparent common mutations were identified.…”
Section: Discussionmentioning
confidence: 77%